Transitivity in Linguistics Abstracts Papers of 2nd LLTC by ELESP - Christine Permata Sari; Maria Evita Sari (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
In linguistic field, transitivity is widely used to analyze newspaper, short stories, novels or other discourses to construe the ideology of the discourses. This research aims to analyze the transitivity processes in abstracts. The data are obtained from abstract papers submitted in 2nd LLTC held by ELESP Sanata Dharma University. The data are analyzed by using qualitative and quantitative methods since the research provides the descriptive analysis based on the percentage of occurrence of the findings. There are five abstracts chosen randomly from twenty linguistics abstracts. The results show that (1) there are six transitivity processes analyzed; material (62.4%), relational (24.7%), verbal (5.4%), mental (4.3%), behavior (3.2%), existential (1.1%) and (2) there thirteen circumstantial elements with the highest percentage is place (54.4%), and the least are frequency, commutative, and matter (1.3% for each). This research can be the initial state of conducting a research on transitivity process and circumstantial elements in abstracts.